1973
DOI: 10.21273/jashs.98.4.357
|View full text |Cite
|
Sign up to set email alerts
|

Foliage Canopy Development of ‘Mcintosh’ Apple Hedgerows in Relation to Mechanical Pruning, the Interception of Solar Radiation, and Fruiting1

Abstract: The percentage of solar radiation passing through the foliage canopy of ‘Mcintosh’ hedgerows, A) pruned annually by cutterbar and B) pruned by slotting saw, was measured continuously from pre-bloom until the completion of foliage growth in late July. Assuming the spur leaf canopy (Sp), emerges first and virtually completes growth before the shoot leaf canopy (Sh), emerges, the relative extent of Sp and Sh, and their respective interception of radiation is calculated at approximately 4-day intervals during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 3 publications
2
11
0
Order By: Relevance
“…Apple leaves which develop in heavy shade, as often occurs inside a large apple tree, are probably quite different from leaves developing in full sun. Considering the seasonal development of an apple tree canopy, early-formed leaves within the canopy pass through a transition from high illumination in the spring to much lower illumination by the time of terminal bud formation (7). It appears that SLW is a useful index and might be more Postharvest CaCl2 dips increase flesh Ca levels in apple fruit and significantly decrease the incidence of breakdown in 'Spartan' apple (3,4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apple leaves which develop in heavy shade, as often occurs inside a large apple tree, are probably quite different from leaves developing in full sun. Considering the seasonal development of an apple tree canopy, early-formed leaves within the canopy pass through a transition from high illumination in the spring to much lower illumination by the time of terminal bud formation (7). It appears that SLW is a useful index and might be more Postharvest CaCl2 dips increase flesh Ca levels in apple fruit and significantly decrease the incidence of breakdown in 'Spartan' apple (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…To affect metabolic disorders, Ca applied to the skin of the apple must move to the appropriate intra-or extracellular sites in the internal tissue. A number of researchers have determined factors which influence the total amount of Ca which can be introduced into apple fruits by postharvest dips (5,7), but there is little information concerning rate of move ment of Ca into the fruit or factors which affect rate of pene tration.…”
Section: Discussionmentioning
confidence: 99%
“…Among reproductive shoots, moreover, those which developed from buds on exposed shoots had more inflorescences per shoot than those from shaded shoots. Researchers and horticulturists have long observed that withincanopy shading can result in a decline in'the productivity of interior shoots or spurs (2,11). In kiwifruit, flower differentiation is contemporaneous with shoot elongation in spring.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the bases of yield in many agricultural crops has indicated the importance of early leaf area development for growth and support of the reproductive phases (20,26). The leaf area in apple develops quickly in the spring (4,18) due to reserves and the preexisting tree structure; however, flowering and fruit set also occur early, prior to complete leaf area development.…”
mentioning
confidence: 99%
“…There is little detailed data available on leaf area development despite its apparent importance prior to fruit set (4,21), especially in relation to reproductive develppment and how pruning may affect it. Therefore, the objectives of this study were to compare the leaf area development in young, bearing apple trees that were unpruned (mostly spur leaves) and moderately pruned (a relative balance of spurs and extension shoots) and to determine if fisheye photography can be correlated to leaf area development.…”
mentioning
confidence: 99%